2010
DOI: 10.1103/physrevb.82.115435
|View full text |Cite
|
Sign up to set email alerts
|

Competing strain effects in reactivity ofLaCoO3with oxygen

Abstract: Planar strain effects on oxygen-vacancy formation and oxygen adsorption on LaCoO 3 are shown to manifest through competing mechanisms. Through first-principles calculations, we demonstrate that these unit processes are facilitated by elastic stretching. On the other hand, spin-state transitions and Co-O bond exchange hinder these processes by trapping the lattice oxygen with increasing tensile strain. A transition from chemisorption to physisorption of the oxygen molecule is identified at high strains. Insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 35 publications
9
89
0
Order By: Relevance
“…Both BM-SCO and P-SCO ozone films were subsequently annealed in-situ at 300 ºC in 500 Torr of O 2 for 5 minutes to explore the effects of strain in a highly oxidizing atmosphere known to convert unstrained SCO to the nearly stoichiometric perovskite. [23,25] As was reported elsewhere, [20,22] such annealing time and environment is known to fully oxidize samples. In either case, oxygen in BM-SCO or P-SCO ozone is respectively intercalated or deintercalated through the OVCs to approach a thermodynamically stable P-SCO state, where stoichiometry under even high oxygen partial pressure is dependent on strain (see Figure 1).…”
Section: Structural Analysis Of Annealed Bm-sco and P-sco Filmsmentioning
confidence: 88%
See 2 more Smart Citations
“…Both BM-SCO and P-SCO ozone films were subsequently annealed in-situ at 300 ºC in 500 Torr of O 2 for 5 minutes to explore the effects of strain in a highly oxidizing atmosphere known to convert unstrained SCO to the nearly stoichiometric perovskite. [23,25] As was reported elsewhere, [20,22] such annealing time and environment is known to fully oxidize samples. In either case, oxygen in BM-SCO or P-SCO ozone is respectively intercalated or deintercalated through the OVCs to approach a thermodynamically stable P-SCO state, where stoichiometry under even high oxygen partial pressure is dependent on strain (see Figure 1).…”
Section: Structural Analysis Of Annealed Bm-sco and P-sco Filmsmentioning
confidence: 88%
“…[13] This results in E a being composed of the difference between H saddle and H i . While H saddle only slightly lowers with tensile strain, H i significantly increases with tensile strain due to changes in the stabilizing effects of hybridization between Co 3d and O 2p, which are dependent on the Co-O bond length [20] .…”
Section: Strain Control Of Oxygen Activation Energy and Formation Entmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in (by works including that of the authors here) to have a significant impact on facilitating oxygen ion transport, [24][25][26][27][28] vacancy formation, [29][30][31][32] and surface adsorption 27, 30 -specific to this paper's scope are the oxygen vacancy formation, oxygen adsorption and oxygen incorporation kinetics on the (La,Sr)CoO 3 films. 27,30,33 La 2 CoO 4+δ has not been a subject of similar studies to date, and we address the potential effects of strain also in this material as part of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the migration of oxygen vacancies and adsorbed oxygen were the key ratelimiting steps governing the overall oxygen incorporation kinetics. Planar tensile strain was predicted to reduce the oxygen vacancy formation energy and the oxygen vacancy migration barrier and strengthen oxygen adsorption on the LaCoO (001) surface [164,165]. These results suggest formation of a greater concentration of oxygen vacancies as active sites, an enhanced mobility of these sites on the surface, and a greater surface coverage of oxygen.…”
Section: Strain Segregation and Reactivitymentioning
confidence: 61%